Nutritive requirements of Dwarf sheep and goats - Velez-Nauer, M. (International Livestock Centre for Africa, 1981)
Presents data on the nutritive requirements of small ruminants. Includes data on dry matter, digestibility, maintainance, growth, body composition, milk production, pregnancy and growth.